Inoculation of Weaned Pigs by Feed, Water, and Airborne Transmission of Salmonella enterica Serotype 4,[5],12:i:- - Olivia L. Harrison; Jordan T. Gebhardt; Chad B. Paulk; Brandon L. Plattner; Jason C. Woodworth; Susan Rensing; Cassandra K. Jones; Valentina Trinetta (Kansas Agricultural Experiment Station Research Reports, 2022)
Salmonella entericaserotype 4,[5],12:i:- (STM) has become an increasing problem for food safety and has been often detected in pork products. For this study, weanling pigs were exposed to STM-contaminated feed, water, or air to determine possible STM transmission routes. An uninoculated control group of pigs was included. The STM was monitored daily in feces and rectal and nasal swabs. The STM colonization was most prevalent in tissues from tonsil, lower intestine, and mesenteric lymph nodes. No differences in lesion severity were observed between inoculated and control pigs. Contaminated feed, water, and aerosolized particles caused infection in weaned pigs; however, no STM colonization was observed in skeletal muscle destined for human consumption. Based on the results from this study, STM contamination in pork products most likely results from cross-contamination of meat by digesta or lymph node tissue during processing.
Keywords: Salmonella Typhimurium; feed; monophasic; swine